LAT1 (SLC7A5) Overexpression in Negative Her2 Group of Breast Cancer: A Potential Therapy Target - Bodoor, Khaldon; Almomani, Rowida; Alqudah, Mohammad; Haddad, Yazan; Samouri, Walaa (Asian Pacific Journal of Cancer Prevention, 2020)
OBJECTIVE: HER2 negative carcinomas of the breast pose a challenge for treatment due to redundancies in potential drug targets and poor patient outcomes. Our aim was to investigate the role of L-type amino acid transporter - LAT1 as a potential prognosticator and a drug target. METHODS: In this retrospective work, we have studied the expression of LAT1 in 145 breast cancer tissues via immunohistochemistry. Overall survival analysis was used to evaluate patient outcome in various groups of our cohort. RESULTS: Positive LAT1 expression was found in 27 (84.4%) luminal A subtype, 27 (64.3%) luminal B/triple positive subtype, 29 (82.9%) triple negative subtype, and 24 (66.7%) HER2-only positive subtype (p=0.1). Interestingly, negative correlation was found between LAT1 and HER2; where positive expression of LAT1 was found in 56 (83.6%) cases in negative HER2 group and 51 (65.4%) cases from positive HER2 group (p=0.01). Unfortunately, we were unable to report significant survival differences when LAT1 expression was studied in the negative HER2 group. Nevertheless, five incidents of mortality (out of 55) were reported in LAT1+/HER2- group compared to none in the LAT1-/HER2- group (N=11). CONCLUSION: Our findings of overexpression of LAT1 in negative HER2 group suggest a role of this protein as prognosticator and drug target in a challenging therapeutic cohort. .
Keywords: regulace genové exprese u nádorů; dospělí; nádorové biomarkery; Large Neutral Amino Acid-Transporter 1; Prognosis; senioři nad 80 let; invazivní růst nádoru; Biomarkers, Tumor; Neoplasm Invasiveness; retrospektivní studie; Humans; Receptors, Estrogen; lidé středního věku; lokální recidiva nádoru; následné studie; Carcinoma, Ductal, Breast; Aged, 80 and over; Carcinoma, Lobular; Middle Aged; míra přežití; Receptors, Progesterone; receptory progesteronu; prognóza; Follow-Up Studies; Receptor, ErbB-2; Neoplasm Recurrence, Local; duktální karcinom prsu; Survival Rate; receptor erbB-2; Adult; Gene Expression Regulation, Neoplastic; lymfatické metastázy; triple-negativní karcinom prsu; Lymphatic Metastasis; ženské pohlaví; přenašeč velkých neutrálních aminokyselin 1; receptory pro estrogeny; lidé; Aged; senioři; Retrospective Studies; lobulární karcinom; Triple Negative Breast Neoplasms; Female